Ancient Tasks of the Great Steppe and Their Place in Boltirik Sheshen’s Work - Baybekov С.Н.; Shormakova С.М.; Ayazbekova Э.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
In the article, Veliko Stefi plays a role in oratorical art, in the volume of literary works of the composer. In the country there are many troublesome problems of the Great Stephen, connected with the Chechen name, and in the age of the greatness of the Kazakh people, the horizons are great and high. Feelings of perfection, mugestvo, красноречии и близости к есть изведующий art are still studied in the science. The Chechen chechen frequently used logic in his traditional practice. This report is distinguished by its logical scale and claustrophobia. The report has been postponed to a press-secretary in Chechnya. The people of the Great Steppe have kept clear and clear the memories of the logic agreed upon. The reason for this is that the Chechen report was of a high, meaningful and systematic thought. At the same time, the solution to the problem is also reasonable and motivated.